Effect of sucrose esters on the crystallization behavior of bulk oil systems - Martini, Silvana (2004)
Sucrose esters (SE) of FA can be used in foods as emulsifiers because they are nontoxic, tasteless, odorless, and are digested to sucrose and FA in the stomach. They can also be used in pharmaceuticals and cosmetics and in other products where a nonionic, nontoxic, biodegradable emulsifier is required. In addition to their major function of producing and stabilizing emulsions, SE have numerous other functional roles as texturizers, film formers, and modifiers of bulk-phase crystallization behavior (with bulk phase meaning a homogeneous oil phase). A few reports have dealt with the effect of SE on the crystallization behavior of fats and oils in bulk systems; however, some of these results vary and may be contradictory. It is of great interest to study the effects of SE on bulk fat systems, particularly with regard to their use in products such as chocolate and confections